2003
DOI: 10.1021/cm0217396
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Comb Polysiloxane Polyelectrolytes Containing Oligoether and Perfluoroether Side Chains

Abstract: Comb polyelectrolytes consisting of a polysiloxane backbone with tetraglyme and lithium-sulfonate terminated perfluoroether side chains have been synthesized. Both types of side chains were independently prepared with allyl functionality and attached to poly(methylhydrosiloxane) by hydrosilylation. Several methods are described to form lithium sulfonate from sulfonate esters. Spectroscopic and thermal characterizations of the resulting polyelectrolyte are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 49 publications
0
48
0
Order By: Relevance
“…They found that the ionic transference numbers and diffusion coefficients were increased with the increase of the length of the EO side chain. Shriver et al [458][459][460] synthesized comb polyelectrolytes consisting of a polysiloxane backbone with EO and single-ion side chains. The detailed discussion will be shown in Section 4.4.…”
Section: Silane or Siloxane Corementioning
confidence: 99%
“…They found that the ionic transference numbers and diffusion coefficients were increased with the increase of the length of the EO side chain. Shriver et al [458][459][460] synthesized comb polyelectrolytes consisting of a polysiloxane backbone with EO and single-ion side chains. The detailed discussion will be shown in Section 4.4.…”
Section: Silane or Siloxane Corementioning
confidence: 99%
“…12 An effective approach to increasing the lithium transference number is to chemically attach the anions on the polymer chains, limiting anion mobility and constructing a single ion conductor. 13,14,15,16 A good anion structure should enable the dissociation between the lithium cation and counter-ion, which could increase the mobile lithium cation concentration in the electrolyte. A salt such as TFSI has an interesting structure that can be used in the construction of single ion conductors.…”
Section: Introductionmentioning
confidence: 99%
“…For example, methacrylic monomers, epoxy resins, polyethers, polyesters, polysiloxane and soybean oils containing CF 3 or CF 2 groups have been synthesized, and their properties, such as glass transition temperature, thermal stabilities, water impermeability, mechanical properties, chemical resistance, surface and optical properties have been studied. [9][10][11][12][13][14][15] These polymers can be cured with ultraviolet (UV) radiation which is an environmentally friendly processing technique, which has advantages, such as room temperature operation, high efficiency, low energy consumption and low pollutions. [16][17][18][19][20] However, studies on fluorinated structures in UV-curable MMA coatings have been relatively seldom.…”
Section: Introductionmentioning
confidence: 99%